Do Postal Stamps (Still) Lead to a Higher Response Rate? An Empirical Test in Belgium. Issue 1 (February 2023) - Hooghe, Marc; Stiers, Dieter
When conducting a postal survey, a traditional recommendation is to use paper postage stamps instead of an automated postage system, to make sure that invitations have a more personal and attractive appearance. In this research note, we investigate whether this traditional recommendation is still valid. In the autumn of 2020, a postal survey was conducted among high-school teachers in Belgium strictly adhering to the Dillman protocol. The overall response rate was 43.4%. Invitations with a real paper postage stamp had a three-percentage points higher response rate (44.9% versus 41.8%), but this difference proved not to be significant. There are no significant gender or age differences between the groups. In addition, the presence or absence of a paper stamp did not influence the respondents' choice for answering the questionnaire online or on paper, as those who received a stamped envelope were equally likely to choose the online answering tool.